ANALYSIS OF INFLATION AND RUPIAH EXCHANGE RATE ON STOCK TRADING VOLUME THROUGH STOCK PRICE AS INTERVENING VARIABLE - Mayliza, Riri; Mulyadi, Olandari; Ilyas, Andre; Yerismal, Yerismal (Jurnal Apresiasi Ekonomi, 2025)
This research examines the effects of inflation and the rupiah exchange rate on stock trading volume, with stock price acting as a mediating variable on BUMN companies listed on the Indonesia Stock Exchange (IDX) from 2017 to 2023. Employing quantitative analysis, the studys population includes all BUMN companies listed on the IDX 2017-2023. A purposive sampling method was applied, yielding a sample of 29 companies. Secondary data were obtained from www.idx.co.id and www.investing.com. The analysis utilized panel data regression through Eviews 12. The results indicate that inflation significantly and positively affects stock prices, while the rupiah exchange rate has a significant negative impact on stock prices. Inflation also significantly and negatively affects stock trading volume, On the other hand, the volume of stock trading is significantly positively impacted by both the rupiah exchange rate and stock price. However, stock prices does not operate as a mediator between the impact the volume of stock trading by inflation and the rupiah exchange rate for BUMN companies listed on the IDX from 2017 to 2023.